Platelets in Host Defense: Experimental and Clinical Insights. Issue 10 (October 2019) - Nicolai, Leo; Gaertner, Florian; Massberg, Steffen
Abstract : Platelets are central players in thrombosis and hemostasis but are increasingly recognized as key components of the immune system. They shape ensuing immune responses by recruiting leukocytes, and support the development of adaptive immunity. Recent data shed new light on the complex role of platelets in immunity. Here, we summarize experimental and clinical data on the role of platelets in host defense against bacteria. Platelets bind, contain, and kill bacteria directly; however, platelet proinflammatory effector functions and cross-talk with the coagulation system, can also result in damage to the host (e.g., acute lung injury and sepsis). Novel clinical insights support this dichotomy: platelet inhibition/thrombocytopenia can be either harmful or protective, depending on pathophysiological context. Clinical studies are currently addressing this aspect in greater depth. Highlights: In mice, platelets contribute substantially to host defense against bacteria by binding, bundling, and containing pathogens. By linking innate immune responses to coagulation, platelets can limit the systemic spread of bacteria in animal models, a process termed 'immunothrombosis'. As first responders, murine platelets are central to the recruitment, activation, and extravasation of innate immune cells, while at the same time preserving vascular integrity. Platelet proinflammatory effector functions can also lead to damage to the host, particularly in severe murine infection models. Clinical data underline the important role of platelets in host defense, with context-dependent beneficial as well as detrimental effects of platelet function.